PEMBALUT WANITA RAMAH LINGKUNGAN DAN BERETIKA - Zamani, Istiqomah Shariati; Husna, Laila Alfi; Yulianingtyas, Aning (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Sanitary napkins during menstruation is a primary requirement. According to the research, disposable sanitary napkin that is now being used contain hazardous substances that could potentially cause disease harmful to the reproductive organs. In addition, there is no special handling for waste disposable sanitary napkins. Although there are safe cloth napkin products, but they are expensive. This program aims to create innovative sanitary napkins are economical, safe, does not cause interferencee for environment and aesthetics. This Innovation Sanitary Napkins made of old cloth. The method used are designing, manufacture and testing. The results are two kind of design (long and wallet), handbags, socialization, banners, and brochures.